2014
DOI: 10.1021/es403491k
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Cyanotoxin Microcystin Arising from Interspecific Differences in Feeding Habits among Fish and Shellfish in the James River Estuary, Virginia.

Abstract: The cyanotoxin, microcystin (MC), is known to accumulate in the tissues of diverse aquatic biota although factors influencing exposure, such as feeding habits and seasonal patterns in toxin production, are poorly known. We analyzed seasonal variation in the MC content of primary and secondary consumers, and used dietary analysis (gut contents and stable isotopes) to improve understanding of cyanotoxin transport in food webs. Periods of elevated toxin concentration were associated with peaks in the abundance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…There are some commercially available kits such as Ridascreen TM test kit (R-Biopharm, Darmstadt, Germany) for PSP toxins, DSPcheck kit (UBE Industries, Tokyo, Japan) and Rougier Biotech ELISA (Montreal, Quebec, Canada) for DSP toxins, ADDA ELISA kit for MCs and NOD (Abraxis, Warminster, PA, USA), and Cigua-Check for CTX toxins (Oceanit Test System, Hawaii, USA) [10,13,26,53,54] Cell-based assays employ live mammalian cells, which are based on cellular response that incorporates both binding to the receptors and subsequent intracellular signaling responses of the cell. Cellular assays rely on a number of end-points, including morphological change, or more commonly cytotoxicity and reporter gene activation [10].…”
Section: Established and Newly Developed Bioassays For Algal Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some commercially available kits such as Ridascreen TM test kit (R-Biopharm, Darmstadt, Germany) for PSP toxins, DSPcheck kit (UBE Industries, Tokyo, Japan) and Rougier Biotech ELISA (Montreal, Quebec, Canada) for DSP toxins, ADDA ELISA kit for MCs and NOD (Abraxis, Warminster, PA, USA), and Cigua-Check for CTX toxins (Oceanit Test System, Hawaii, USA) [10,13,26,53,54] Cell-based assays employ live mammalian cells, which are based on cellular response that incorporates both binding to the receptors and subsequent intracellular signaling responses of the cell. Cellular assays rely on a number of end-points, including morphological change, or more commonly cytotoxicity and reporter gene activation [10].…”
Section: Established and Newly Developed Bioassays For Algal Toxinsmentioning
confidence: 99%
“…It is also evident that various algal toxins might predominate in different water bodies. Seasonal variations of MCs in the tidal freshwater segment of the James River Estuary, for example, occurred with first peak in May, maximal concentration in July and August, and undetectable after November, concurrent with the abundance of Microcystis and the mcyD genes responsible for MC generation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Microcystis ADDA-ELISA < 0.10 µg/L (May), 0.92 µg/L (July), < 0.05 µg/L (Nov) [13] Monterey Bay, California, USA…”
Section: Mcsmentioning
confidence: 99%
“…There are some commercially available kits such as Ridascreen TM test kit (R-Biopharm, Darmstadt, Germany) for PSP toxins, DSPcheck kit (UBE Industries, Tokyo, Japan) and Rougier Biotech ELISA (Montreal, Quebec, Canada) for DSP toxins, ADDA ELISA kit for MCs and NOD (Abraxis, Warminster, PA, USA), and Cigua-Check for CTX toxins (Oceanit Test System, Hawaii, USA)[10,13,26,53,54]. More methods are being developed toward commercial ELISA kits in detecting various algal toxins.…”
mentioning
confidence: 99%
“…But is it absolutely safe when there is no obvious bloom? A study in the James River Estuary indicated that potential health risks may exist in non-bloom periods [ 34 ]. Another study in the San Francisco Estuary indicated that Microcystis , even at low abundance, may have influences on fishery production via toxic and food web at multiple trophic levels [ 35 ].…”
Section: Introductionmentioning
confidence: 99%